Current concepts in the primary management of irreparable posterosuperior rotator cuff tears without arthritis. Issue 5 (21st May 2018) - Lädermann, Alexandre; Collin, Philippe; Athwal, George S.; Scheibel, Markus; Zumstein, Matthias A.; Nourissat, Geoffroy
Abstract : Various procedures exist for patients with irreparable posterosuperior rotator cuff tears (IRCT). At present, no single surgical option has demonstrated clinical superiority. There is no panacea for treatment and patients must be aware, in cases of palliative or non-prosthetic options, of an alarming rate of structural failure (around 50%) in the short term. The current review does not support the initial use of complex and expensive techniques in the management of posterosuperior IRCT. Further prospective and comparative studies with large cohort populations and long-term follow-up are necessary to establish effectiveness of expensive or complicated procedures such as superior capsular reconstruction (SCR), subacromial spacers or biological augmentation as reliable and useful alternative treatments for IRCT. Cite this article: EFORT Open Rev 2018;3 DOI: 10.1302/2058-5241.3.180002